Clinical features non-coeliac gluten sensitivity in children - N.M. Kazytska (Zaslavsky O.Yu., 2018)
The article presents the results of clinical and laboratory examination of 19 children aged 7 months to 7 years who were diagnosed with non-coeliac gluten sensitivity. The intestinal and extra-intestinal symptoms in this disease are analyzed. A step-by-step diagnostic strategy for the diagnosis of non-coeliac gluten sensitivity is presented.